Memories and Stories: the formation of Mathematics teachers in Montes Claros - MG (1960-1990) - Shirley Patrícia Nogueira de Castro e Almeida; Maria Laura Magalhães Gomes (Universidade Federal do Oeste da Bahia, 2020)
This doctoral research aimed to investigate the history of the formation of mathematics teachers in northern Minas Gerais, in the undergraduate course at the current State University of Montes Claros - UNIMONTES. The focused period extends from the 1960s to the 1990s. We used the Oral History methodology, according to the parameters of the Oral History and Mathematical Education Group - GHOEM, integrating the project he developed to map the training and performance of teachers of Mathematics in Brazil. The examination of the interviews carried out shows us a great search for the expansion of the staff of graduated teachers to work in Basic Education and, also, that the graduates to become teachers of the course/institution that had trained them.